2023
DOI: 10.1515/ract-2023-0154
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in correlating oxygen stable isotope ratios of hydrates on uranium ore concentrates to process waters

Abstract: Exchange of oxygen stable isotopes (δ18O values) between precipitation waters and uranium oxides is governed by thermodynamics or kinetics. It has been assumed that meteoric waters can be related to precipitation waters in uranium ore concentrates and their calcined and reduced uranium oxide products. With this assumption, the δ18O values of uranium materials could provide forensic signatures that identify the production history and geolocation of nuclear materials. To further exploit the potential of δ18O val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…A 2001 study by Pajo et al found that δ 18 O values of collected UO 2 pellets matched closely that of the local meteoric waters (rain and snow) where the pellets originated. 14 More recently, Klosterman et al examined the fractionation between uranyl peroxide and ADU with the water, from which these compounds were precipitated, along with the changes in δ 18 O values after calcination in dry air and an inert nitrogen atmosphere. 12 preferentially exchanged oxygen with water vapor at 400 °C.…”
Section: ■ Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…A 2001 study by Pajo et al found that δ 18 O values of collected UO 2 pellets matched closely that of the local meteoric waters (rain and snow) where the pellets originated. 14 More recently, Klosterman et al examined the fractionation between uranyl peroxide and ADU with the water, from which these compounds were precipitated, along with the changes in δ 18 O values after calcination in dry air and an inert nitrogen atmosphere. 12 preferentially exchanged oxygen with water vapor at 400 °C.…”
Section: ■ Introductionmentioning
confidence: 86%
“…15 More recently, Assulin et al studied oxygen isotope exchange between U 3 O 8 and atmospheric O 2 at a range of temperatures and found that oxygen exchange between U 3 O 8 and O 2 was minimal below 100 °C, partial exchange occurred between 100 and 200 °C, and isotopic equilibrium was reached above 400 °C. 16 They also found that preferential incorporation of 16 O by U 3 O 8 led to U 3 O 8 attaining δ 18 O values lower than O 2 . Expanding this work, they calcined three U 3 O 8 samples of differing δ 18 O values to UO 2 between 500 and 700 °C for 2, 4, and 6 h. 17 From these experiments, they found that the final δ 18 O values of the UO 2 were dictated by the isotopic equilibrium between the water generated during the reduction and the resultant UO 2 .…”
Section: ■ Introductionmentioning
confidence: 94%
See 3 more Smart Citations